PELAYANAN PERPUSTAKAAN PADA KANTOR PERPUSTAKAAN DAN ARSIP DAERAH KABUPATEN HULU SUNGAI UTARA - Sugianor Sugianor (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2014)
The central issue in this study is the lack of support facilities such as facilities and infrastructure such as the number of books is still limited and the quality and quantity of employees that are still lacking. This study aims to: (1) To know know the quality of library services In Office Regional Library Upper North River, (2) To determine what factors influence in providing library services to the Office of Regional Library Hulu Sungai Utara. The method used in this study were A study to provide a detailed overview of the background, the nature, characteristics, typical of the quality of library services in providing public services to the community. Collecting data with interview techniques, observation and documentation. Analysis of the research results are used qualitative analysis with data reduction step, the presentation of the data and draw conclusions.The results showed: (1) Library and Archives Services Hulu Sungai Utara Regency is quite good, especially in the aspect of Assurance (Assurance) and Empathy (Empathy) and DayaTanggap (Responsiveness), while the aspect needs to be improved is the Physical Evidence (Tangibles) and reliability (Reability) is a collection of books and appropriate facilities and infrastructure supporting the development of ICT (Information Communication and Technology as well as knowledge and education for the improvement of the quality of employees. (2) Factors that affect library and archive service Hulu Sungai Utara Regency is a means and infrastructure such as collection of books as well as the quality and quantity of employees Library and Archives Hulu Sungai Utara Regency inadequate. Keywords: Service Quality and Library